Neural circuits underlying auditory contrast gain control and their perceptual implications - Michael Lohse (Nature Portfolio, 2020)
Auditory contrast gain control helps us perceive sounds as constant despite changes in the environment or background noise. Here, the authors show that neurons in the auditory thalamus and midbrain of mice display independent contrast gain control, not just the cortex as previously thought.